Opowieść o koniu, który ani piękny, ani duży, ale wytrzymały był (HA., Prob., 8) - BARANOWSKI, Michał (Historia i Świat, 2014)
The present paper discusses a peculiar fragment in”Historia Augusta” (v. Probi 8) concerning the gift of a horse to Probus from his soldiers. According to former scholars, it represents nothing else than a literary topos. Consequently, the passage has not been the object of much interest to contempo-rary historians. However, the author argues that, irrespectful of its authenticity, this anecdote may constitute a key to proper understanding of Probus’s image created in “Historia Augusta”. Thus, on one level of analysis, the story serves as a means of presenting an idealised image of the emperor. On the other hand, it may also be considered as an omen imperii.